Comparison of Surgical Outcomes Between Video-Assisted Anal Fistula Treatment and Fistulotomy Plus Seton for High-Lying Perianal Fistula - Rizvi, Taskeen Zehra; Sheikh, Prof. Dr. Muhammad Ayyaz; Umar, Muhammad; Akram, Tanzeela (Indus Journal of Bioscience Research, 2025)
Introduction: This study aims to compare video-assisted anal fistula treatment with fistulotomy plus seton in the management of high perianal fistula in terms of postoperative outcomes. There is limited research on the treatments of high-lying perianal fistulae. This study will help us improve pain severity, return the patients to regular work, improve healing time, and reduce the recurrence rate, leading to better patient management. Study Design: Randomized controlled trial. Study Period: From July 20, 2024, to January 19, 2025. Methodology: There were 60 patients of high-lying perianal fistulae, ranging in age from 18 to 60 years. Patients having a history of prior perianal surgery, a medical record-based history of inflammatory bowel disease, uncontrolled diabetes, or a lump on a digital rectal examination that suggested malignancy were excluded. All the patients were assigned to two groups using an online randomizer, i.e., Group A were undergone video-assisted anal fistula treatment, and Group B were undergone fistulotomy plus seton. Postoperative pain was determined 6 hours after the surgery using the visual analogue score. Patients were followed up in the outpatient clinic at three months to determine healing status, anal incontinence and recurrent rate. Findings: Group A (VAAFT) experienced mean post-operative pain of 5.41 ± 1.89, whereas Group B (fistulotomy plus seton) experienced mean post-operative pain of 3.24 ± 1.29 (p-value = 0.0001). In Group A (VAAFT), the mean healing time was 38.40 ± 5.25 days, whereas in Group B (fistulotomy plus seton), it was 25.93 ± 4.30 days (p-value = 0.0001). 33.33% and 0.0% of patients in group A (fistulotomy plus seton) experienced post-operative pain and anal incontinence, respectively, whereas 13.33% and 0.0% of patients in group B (fistulotomy plus seton) did the same. Conclusion: VAAFT is a novel sphincter-saving procedure used to treat high perianal fistulas.